Love Cures Healing and Love Magic in Old French Romance - Doggett, Laine E.; Project Muse. (Pennsylvania State University Press, 2009)
"Examines literary portrayals of women who practice healing and love magic, and argues that these figures were modeled on informally trained practitioners common in the magico-medical paradigm of the high Middle Ages, and were well-respected and successful"--Provided by publisher.
Introduction -- Background considerations -- On artifice and realism : Thessala in Chretien de Troyes's Cliges -- Tristan and Iseut : beyond a symbolic reading of empirical practice -- Tristan and Iseut : empirical practice amidst competing claims -- Love and medicine in the Roman de silence -- Reworked elements in Amadas et Ydoine -- Conclusion.
Includes bibliographical references (p. [268]-286) and index.
Description based on print version record.
Keywords: Healing in literature; Love in literature; Magic in literature; Women healers in literature; French literature -- To 1500 -- History and criticism; Romances -- History and criticism; Electronic books